Inelastic collisions of CaH with He at cryogenic temperatures - Singh, V.; Hardman, K.; Lu, M.; Ellis, Aja; Morrison, M.; Weinstein, J. (Taylor & Francis Ltd., 2013)
Using helium buffer gas cooling, we have prepared dense samples of ground-state molecular calcium monohydride (CaH X 2Σ) at cryogenic temperatures. We have used optical pumping to polarise the spin state of the CaH molecules and we have measured the inelastic collisions of molecular CaH with atomic helium at temperatures from 2 to 7 K. The measured CaH electronic spin depolarisation rate coefficient increases rapidly with increasing temperature, increasing from 2 × 10−13 cm3 s−1 to over 10−11 cm3 s−1. The strong dependence of rate coefficient on temperature is attributed to the CaH population in the first excited rotational state.